How to succeed as an athlete: what we know, what we need to know - Foster, C.; Barroso, R.; Beneke, R.; Bok, D.; Boullosa, D.; Casado, A.; Chamari, K.; Cortis, C.; de Koning, J.; Fusco, A.; Haugen, T.; Lucía, A.; et al. (International Journal of Sports Physiology and Performance, 2022)
When I (C. Foster) was in my teens, I was a runner. While any objective observer would have known that my prospects for Olympic medals or world records were low, I had "delusions of grandeur" and believed that I might find the right combination of knowledge and effort to succeed. That never happened. However, that passion and quest for success led to my professional career. For many of us, the same quest to achieve "the impossible dream" drove our professional careers (only 2 of us [A. Casado and K. Chamari] were Olympians, so we are better as scientists than athletes). This same mindset is, to some degree, the underlying rationale for IJSPP. I asked several of my friends to identify factors necessary for success. In other words, what do we know and what do we need to know? Later, in a more detailed referenced manuscript, we can treat this topic more fully.